RISK ASSESSMENT AND DETERMINANTS OF DIABETES MELLITUS RISK AMONG NURSING STUDENTS: A CROSS- SECTIONAL STUDY - Nurmalisa, Baiq Emy; Sasmita, Hanum; Prayogi , Bisepta; Siregar, Hasbunsyah (International Archives of Medical Sciences and Public Health, 2025)
Type 2 Diabetes Mellitus (T2DM) is a growing epidemic among young adults. Nursing students represent a critical population for early risk detection due to their future role in healthcare. This study aimed to assess T2DM risk and its determinants among nursing students. A cross-sectional study was conducted among 100 nursing students at Poltekkes Kemenkes Palu. T2DM risk was assessed using the FINDRISC instrument. Independent variables included BMI, waist circumference, physical activity, family history, and smoking status. Bivariate and multivariate logistic regression analyses were performed. The majority (88%) had mild risk, while 9% had moderate and 3% had severe risk. Central obesity (AOR=32.15; p<0.001), family history of diabetes (AOR=12.76; p<0.001), and overweight/obesity (AOR=8.42; p=0.002) were significant independent predictors of elevated diabetes risk. One in eight nursing students is at moderate-to-severe T2DM risk. Central obesity, family history, and high BMI are key determinants, highlighting the need for targeted screening and preventive lifestyle interventions in this population.